Study of implications of thyroid status over feto-maternal outcomes in pregnancy - Gedam, Smruti; Bhushan, Bharat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Thyroid disorders are reported at clinically significant prevalence during pregnancy, affecting 5% of all pregnancies. Maternal thyroid status during pregnancy purportedly affects fetal as well as maternal outcomes. The objective of present study was to analyse the relationship of thyroid status in pregnancy and various maternal and fetal outcomes. Methods: In this hospital based observational study, a total of 913 pregnant women were enrolled as per fixed criteria and all the study participants were screened for thyroid disorders. Further, they were followed up throughout pregnancy and puerperium and evaluated for various maternal and fetal complications by predefined outcome measures. The results were compared by subgroup analysis. Results: Of the 913 patients screened, 105 were diagnosed with thyroid abnormality and followed up till delivery, with newborn thyroid profile on day 7. Total 49 patients were diagnosed with anaemia (46.66%), of which 46 (43.80%) had subclinical hypothyroidism (p <0.05); along with pregnancy induced hypertension in 42 (40%) cases of which 40 (38.09%) had subclinical hypothyroidism were observed to have statistically significant associations. Intrauterine growth restriction (IUGR) (37, 35.23%) and prematurity (19, 18.1%) were the most common fetal occurrences; the association of IUGR and subclinical hypothyroidism being statically significant. Conclusions: Thyroid disorders during pregnancy are commonly associated with maternal and fetal complications and thyroid profile is recommended as universal screening method in early pregnancy to diagnose and start required treatment early.